TO BE (PRESENT) OR NOT TO BE: THE QUESTION OF FACE-TO-FACE OR ONLINE ORAL ASSESSMENT PREFERENCE AND PERCEIVED PERFORMANCE AMONG UiTM PERLIS STUDENTS - Mansor, Mahani; Maesin, Anis (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Oral skills in language learning appear to be the hardest to master among university students. This is mainly due to learners' apprehension, anxiety and lack of preparedness in speaking the language. The change that happened to the education system after the Covid pandemic has seen a shift from face-to-face class assessment to online assessment in tertiary level education. The question now is do the learners today feel that they are better prepared and more at ease to do oral assessment in English online or do they still prefer the face-to-face assessment in class? Since face-to-face oral assessments have been a norm in the past, it would be interesting to know if they are still preferred by the learners or otherwise. This study, therefore, explores whether language learners in UiTM generally prefer online or face-to-face oral assessment. It also aims to discover the learners’ perceptions on their oral assessment performance online and face-to-face. The participants are 51 UiTM Perlis Branch students who enrolled in English Language Courses (LCC) at a Diploma and Degree levels. They completed a survey that investigates their level of preference, self-confidence, and perceived performance in oral assessments conducted face-to-face and online. Findings suggest that the students generally prefer online oral assessments but in terms of perceived performance, their views were mixed between the face-to-face and online assessments. The results of the study are theoretically significant as they identify the students’ preference in oral assessments. They also provide insights for course developers, the policy makers and language instructors to optimize students’ achievements in their oral assessments.